Mother and Family's View on Exclusive Breastfeeding in Developing Country - Iqbal Pramukti; Michael Hil; Norehan Binti Mohammad Isa (Universitas Padjadjaran, 2017)
Exclusive breastfeeding is something which has a lot of benefit both for mother and baby. It is recommended by WHO at let for the first six months. Then it also recommended until two years and beyond. In fact, mostly mother only gave their breastmilk to their babies until two months. The method of this study using systematic review-metasynthesize which an extensive of the literature was undertaken. Database searched were: MEDLINE, CINAHL, BioMed Central, Wiley, and EMBASE. Result shown that mother's view on exclusive breast is an important part in an attempt to promote breastfeeding desire. Even though their view is influenced by her family and surroundings, but finally the decision is on her. This concurs with finding of some researcher who found women who have the experience of breastfeeding, especially within the family, are more likely to choose to breastfeed heir child.